There Goes the Neighborhood: Exposing the Relationship Between Gentrification and Incarceration - Kellogg, Casey (2015)
This paper seeks to demonstrate that there is a deliberate and intentional link between residential housing patterns and crime and mass incarceration, and that government plays a strong role in allowing and formalizing this link. Using historical examples, this paper attempts to document the role of government and policy in furthering residential segregation through the processes of gentrification and disinvestment. By contributing to the destruction of low-income communities and the invasion of gentry through covert partnerships with the private sector to develop land and design cities, government has prioritized commercial interests over the needs of the community at all income levels. Finally, this paper examines the role of gentrification in defining criminal behaviors among communities, the effects of increased police surveillance, and the impact on perceived crime rates